Cruising after a Covid-19 Pandemic: Factors Influencing Tourists’ Purchase Intention - Liqun Chen; Victor Wee; Jeetesh Kumar (ASEAN Journal on Hospitality and Tourism, 2023)
The global cruise tourism industry has been significantly impacted by the COVID-19 pandemic. As a result, it is important to understand the factors that affect tourists' decision to purchase cruise holidays after the pandemic. To accomplish this, a conceptual model based on the perceived value theory and incorporating concepts such as destination image, perceived risk, and purchase intention is proposed. This framework can be utilized to investigate tourists' purchase intention for cruise holidays and assist the cruise tourism industry in devising appropriate policies and designing cruise tourism products. This study is the first to develop a model for tourists' purchase intentions for cruise holidays after the COVID-19 outbreak.